Printing House of the Vilnius Academy and Censorship of Books - Petrauskienė, Irena (Knygotyra, 1973)
In all times the spreading of book and the contests of it were conditioned by censorship. It was very obvious at the beginning of the printing era, when almost every book had to be an ideological weapon in the area of the struggle between religion or politics. The censorship reigned over the books, printed in the Vilnius Academy printing house, which functioned in the period of 1576–1773. All the printed books were under the control of Jesuits.Censors were required to be silent, objective and to know the subject thoroughly. In their work they followed the directions of Jesuits. Meanwhile in practice they were far from impartiality. Censors avenged cruelly with people whose ideology didn’t coincide with theirs. On the other hand they encouraged the works devoted to the ruling class. That’s why anonymous or pseudonymous publications were strictly prohibited, because in such works authors could express their thoughts more boldly.One-sided and strict censorship influenced the contents of books negatively. That’s why books published by the Academy were of similar type, one could feel the narrowness of their contents.Only talented people managed to make their way through the mechanical and scholastic dogmas and left a lot of valuable works for the future generations.